Using nontraditional text for Socratic dialogue in a middle level Montessori music classroom - Bijoch, Stephanie (My University, 2015)
Music is a part of the everyday lives of most people. Ensemble directors and music educators have noticed that many students are music-illiterate. While students enjoy listening to and performing music, many students cannot accurately or thoughtfully describe the thematic ideas that are represented in the music they are listening to. In this study, students participated in three Socratic seminars that used a work of music as the assigned "text." Students were guided through the process of listening to a work of music and making annotations. Various guides and strategies for annotating music were provided. Students participated in open-ended question based discussions that aimed to discover the theme of the music. After the discussions were finished, students reflected on their preparation and participation in Socratic seminar. Annotations, student surveys, teacher observations, and student observations were collected as evidence. Results showed that works of music can successfully be used a "text" for a Socratic seminar, and that Socratic seminars are an effective technique for discussing music.
Plan B Paper. 2015. Master of Science in Education- Montessori--University of Wisconsin-River Falls. Teacher Education Department. 40 leaves. Includes bibliographical references (leaf 31)
Keywords: School music--Instruction and study; Music--Instruction and study; Montessori method of education